The nature of internet : the law and ethics for the Information Society - Olivera, Noemí ([Actas])
This work is aimed to contribute to the definition of the most adequate public actions -policies and laws- that are required to achieve an inclusive Information Society. It seems that such policies should be meant to grant full use of ICTs, but, whereas in developed societies these regulations should be enough, in the underdeveloped ones, the Information Society can only be discussed after the spreading of the ICTs, and this depends on the accuracy of policies aimed at impelling their diffusion. Considering that the Internet is a public good, we evaluate how the universal access to the net should be granted. Then, we analyze the more adequate legal policies for ICT, the Internet and the Information Society. We sum up that, in order to achieve an inclusive Information Society, the universal rights of access to and benefit of Internet for developing countries should be established at an international level.